2016
DOI: 10.3390/agriculture6030033
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change: Seed Production and Options for Adaptation

Abstract: Food security depends on seed security and the international seed industry must be able to continue to deliver the quantities of quality seed required for this purpose. Abiotic stress resulting from climate change, particularly elevated temperature and water stress, will reduce seed yield and quality. Options for the seed industry to adapt to climate change include moving sites for seed production, changing sowing date, and the development of cultivars with traits which allow them to adapt to climate change co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 117 publications
2
19
0
1
Order By: Relevance
“…Plants in water stress conditions cannot properly use high CO 2 concentration as much as those that are well watered, due to the lower stomatal conductance caused by less guard cell turgescence. Therefore, CO 2 uptake will decrease in these plants 12,60 . The difference in seed production between the resistant and susceptible biotypes was not significant in the water-stressed condition at both CO 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Plants in water stress conditions cannot properly use high CO 2 concentration as much as those that are well watered, due to the lower stomatal conductance caused by less guard cell turgescence. Therefore, CO 2 uptake will decrease in these plants 12,60 . The difference in seed production between the resistant and susceptible biotypes was not significant in the water-stressed condition at both CO 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental plant physiological approaches can prove to be beneficial and may finally generate models showing the contribution of different signaling pathways that define "omic" architectural responses to global climatic changes [31]. Studies in the past have recognized an epigenetic contribution related to the adaptation of crops to stressed environments [1,6,9,10,37]. Because seeds are developed in a parental environment, transgenerational epigenetic inheritance provides a mechanism for adaptive parental effects on progeny [38].…”
Section: Discussionmentioning
confidence: 99%
“…Huxman et al [9] found an increased C/N ratio in elevated-CO 2 -developed Bromus rubens L. grass seeds, which resulted in reduced seed quality and seedling performance. Moreover, Hampton et al [10] suggested that elevated CO 2 during seed development might produce greater ethylene, which induces early seed germination in many species. The adverse impacts of high temperatures on seeds during development might be attributed to the limited supply of photosynthetic assimilates [3,11] and physiological damage leading to a loss of seeds' ability to germinate [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…growing season. According to Hampton et al (2016), the variation of climate as expressed in the different growing season could affect the seed mass because of the changes of seed growth rate and seed filling duration.…”
Section: Yield and Yield Attributesmentioning
confidence: 99%